Smart Milan Innovations from Expo to Expo (1906-2015) - Granata, Mattia (Springer eBooks, 2015)
This book celebrates Milan's hosting of the World Exposition (Expo) in 2015 by providing fascinating insights into the city and its history that will appeal to all those visitors to Expo 2015 who wish to understand fully what Milan has to offer and what they are to see there. Combining straightforward language with academic thoroughness, the book traces the evolution of Milan from the previous Expo in 1906 through to the present day. Readers will learn about the innovative contributions made by Milan in many fields, including industry, architecture, scientific research, culture, fashion, design, and food. Today, Milan is a smart city, modern and at the forefront of progress. It is the Italian city always in touch with the world and able to compete with the most progressive foreign cities. During the World Exposition, Milan presents to visitors the best aspects of its history and its way of life. This book is therefore an ideal reference source for visitors seeking to appreciate the past, as well as the potential future, contributions of the city to Italy and the world.